Pollen Interference Between Rare and Common Species - Eva M. Malecore; Markus Fischer (Ecology and Evolution)
ABSTRACT The mechanisms underlying plant species distribution and abundance have been long studied in ecology. However, the role of heterospecific pollen interference in shaping these patterns needs more attention. Species distribution and abundance are important factors determining whether a species is endangered or not; thus, understanding the impact of heterospecific pollen interference on rare species could help to inform conservation strategies aimed at preserving plant communities. In this study, we conducted a multispecies experiment using eight co‐occurring and co‐flowering plant species with varying rarity levels in Switzerland. We performed cross‐pollinations by hand between nearly all species pairs and measured seed set (whether a flower produces seed) and seed number (number of seeds per flower) as outcomes. We looked at the effects of rarity status, self‐compatibility, and recipient‐donor relatedness on heterospecific pollen interference. Contrary to expectations, neither seed set nor seed number were affected by heterospecific pollen deposition. Self‐compatible species had a higher seed set probability, but this was independent from species rarity. In our study setting, heterospecific pollen interference seems to have only minor effects on seed set and seed number, and consequently on recruitment. Thus, heterospecific pollen interference seems to play only a minor role in shaping plant species distribution and abundance. Nevertheless, the higher impact of heterospecific pollen deposition on rare and closely related species, as well as the importance of conspecific pollen loss, might need further investigation for both in situ and ex‐situ conservation strategies.